Does Gender Diversity Moderate Good Corporate Governance on Sustainability Performance? - Tael Batak, Felicia Andrea; Mardiati, Endang; Andayani, Wuryan (The International Journal of Accounting and Business Society, 2025)
Purpose — This study aims to examine the effect of good corporate governance (GCG) on sustainability performance, as well as to examine the effect of gender diversity as a moderating variable Design/methodology/approach — GCG is measured by the size of the board of commissioners, independent commissioners and audit committee. Sustainability performance is measured using content analysis with the help of a checklist. This study uses a sample of financial sector companies listed on the Indonesia Stock Exchange in 2020-2022. Based on the purposive sampling method, 240 observations were obtained during 2020-2022. Findings — First, the size of the board of commissioners has no effect on sustainability performance. Second, independent commissioners and audit committees affect sustainability performance. Third, gender diversity can strengthen the relationship between commissioner size and sustainability performance. Fourth, gender diversity does not moderate the relationship between independent commissioners and audit committees on sustainability performance. Practical implications — Financial sector companies have increased sustainability reporting as evidence of good corporate governance implementation, while the importance of strengthening the role of independent commissioners and audit committees that meet GCG qualifications to improve transparency and sustainability. Companies also need to prioritize increasing gender diversity in board recruitment to support holistic decision-making and better performance. Originality/value — This paper presents corporate governance practices on sustainability performance of financial companies in Indonesia in managing economic, environmental, and social aspects, and introduces gender diversity as a moderating variable that strengthens the relationship between corporate governance and sustainability performance. Keywords — Good corporate governance, sustainability performance, gender diversity Paper type — Case study